Accuracy of a Rationally Derived Method for Identifying Treatment Failure in Children and Adolescents. - Bishop, Matthew J.; Bybee, Taige S.; Lambert, Michael J. (Journal of Child & Family Studies, 2005)
Psychotherapy outcome can be enhanced by early identification of potential treatment failures before they leave treatment. In adults, compelling data are emerging that provide evidence that an early warning system that identifies potential treatment failures can be developed and applied to enhance outcome. The present study reports an analysis of early warning algorithms to identify treatment failures among child/adolescent patients (ages 3–18). The progress of 300 patients who had completed treatment was analyzed to see if algorithms could identify those children who ultimately had a negative outcome. Results indicated that the rationally derived method had a 77% success rate for identifying child/adolescent patients who were reliably worse or had deteriorated by the time that therapy was terminated. Reprinted by permission of the publisher.